Anak Tumbuh Cerdas Dengan Stimulasi Anak Usia Pra Sekolah - Rima Yunitasari RIMA; Amalia Solichati Rizqi; Yudha Wahyu Putra (Kreativasi : Journal of Community Empowerment, 2023)
Children are the next generation of the nation and family, the biggest hope for a family lies in a child. So, it is important for parents to consider their growth and development. Monitoring the growth and development of preschool children is an important phase because it can determine the quality of health, welfare, learning and behaviour in the future. Stimulation is one method for activities to stimulate children's basic abilities so that children grow and develop optimally. This activity aims to overcome the problem of growth and development of preschool children. The method is to provide direct socialization and guidance on stimulating preschool children. Parents, cadres and teachers are expected to be able to apply stimulation of growth and development directly and routinely to children at Taman Merpati IV so that children's growth and development can be more optimal.